BIOPSIKOSOSIAL-SPRITUAL IMPACTS OF SEXUAL ABUSE FOR MINORS IN AMBON CITY - David Marthen Salakory (Sosiohumaniora, 2021)
Sexual abuse against minors is already one of the social ills in people’s lives. Victims of sexual abuse are often exposed in the public and even closed. The victim feels that it is something taboo and can even damage a person’s disgrace. Therefore, they need treatment from institutions that are concerned with social issues that deal with child victims of sexual abuse. This research aimed specifically to determine the impact of the case on child victims of sexual abuse through a biopsychosocial-spiritual approach and to explain the strategy model of psychosocial-spiritual treatment, together with institutional accompaniment, referring children to doctors and being accepted by children of victims of social abuse under age. The method used in this research was a qualitative descriptive study with the type of case study. The study was carried out at the Ambon City Women’s Empowerment Circle (LAPPAN). Data collection was carried out by in-depth interviews and direct observations to the victims in the field and LAPPAN officials. This research shows that victims of sexual abuse occur in underage children in Ambon City aged 9 -12 and 13 -16, which have an impact on biopsychosocial-spiritual. The psychological impact is that the child feels mentally disturbed, while the social impact is related to the child’s relationship in the social environment, both at home and school. The spiritual impact makes children embarrassed to attend worship meetings in places of worship. In addition, LAPPAN provided serious assistance in reducing the psychological problems experienced by the victims.